MOTIVASI PENDERITA HIPERTENSI DI DESA KOBO KECIL MEMANFAATKAN PELAYANAN KESEHATAN DI PUSKESMAS KOTABANGUN - Kanine, Esrom; Pobela, Nelpi (JURNAL KEPERAWATAN, 2018)
Abstrac: Background: Internal and external factors influence motivation to hypertension patiens usingfacilitation at the Puskesmas Kotabangun. The people at Kobo Kecil village including age 30-55 yearold on the survey result showed generally complain dizzyness, nausea and insomnia. not having ahealth insurance card has an impact on the lack of motivation to visit health facilities to check theirblood pressure. Distance with health facilities impact to hypertension patients consumption herbaldrugs.Aims: Identify the motivation of hypertensive patients to using health services at PuskesmasKotabangun. Methods: This research using the design of quantitative research. Seventeen sampleswere recruited using purposive sampling strategy, using cross sectional. Some including age 30-55year old, more than six month suffering from hypertension. Data was analyzed using Chi Square, withp value < 0,05. Result : there was significant relationship between factors of visit, distance toPuskesmas, insurance ownership and socio economic with motivation (p value less than alpha valueof 0.05). While the attitude of health workers is not related to the lower motivation of patients seekingtreatment at the Puskesmas Kotabangun. Conclusion : This findings describes hypertension patientshave lower motivation to use health services at the Puskesmas KotabangunKeywords :Motivation, Hypertension Patients